SLEEP DURATION AND DEPRESSION AMONG ADULTS: A META‐ANALYSIS OF PROSPECTIVE STUDIES - Zhai, Long; Zhang, Hua; Zhang, Dongfeng (Depression and anxiety, 2015)
Background Results from longitudinal studies on sleep duration and incidence of depression remain controversial. Methods PubMed and Web of Science updated on October 22, 2014 were searched for eligible publications. Pooled relative risks (RRs) with 95% confidence interval (CI) were calculated using a random‐effects model. Results Seven prospective studies were included, involving 25,271 participants for short sleep duration and 23,663 participants for long sleep duration. Compared with the normal sleep duration, the pooled RR for depression was 1.31 (95% CI, 1.04–1.64; I2 = 0%) for the short sleep duration overall. For long sleep duration, the pooled RR was 1.42 (95% CI, 1.04–1.92; I2 = 0%). The associations between short or long sleep duration and risk of depression did not substantially change in sensitivity and subgroup analyses. No evidence of publication bias was found. Conclusion This meta‐analysis indicates that short and long sleep duration was significantly associated with increased risk of depression in adults.